Educação artística não formal em públicos adultos - Calado, Margarida, 1947- (2019)
In this paper we reflect about art and heritage education for adult and older people, either attending free classes of History of Art, either in cultural learning in monuments and museums, considering above all our personal experience at SNBA (National Society of fine Arts). We believe that art education for adult people should help to a better way of facing art education in schools, above all when politic power makes us believe that maternal language (Portuguese) and Mathematics are the most important subjects. On the other hand, art education can help to increase the value of our historical heritage and also to improve the interior country through tourism. We also wish to know why people in the end of their professional careers look for art education, or even try to conciliate after — work courses with their professional life. So we have made two little inquiries directed to people attending Art History courses in SNBA and also people participating in Cultural learning travelling in group through our country